2014
DOI: 10.1007/s12026-014-8573-5
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory impairment in patients with the fibromyalgia syndrome and systemic sclerosis

Abstract: Patients with autoimmune diseases often present with olfactory impairment. The aim of the study was to assess the olfactory functions of female patients with fibromyalgia (FM) compared with patients with systemic sclerosis (SSc) and with healthy female controls. Olfactory functions were assessed in 24 patients with FM, 20 patients with SSc and 21 age-matched healthy controls. The sense of smell was evaluated using the Sniffin' Sticks test including the three stages of smell: threshold, discrimination, and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
11
0
1
Order By: Relevance
“…Patients with IICH often show decreased olfactory bulb volumes91 and impaired olfactory function 9. These findings have also been reported for patients with FM 3. It is most likely that these symptoms are due to increased pressure compromising the blood supply and damaging the olfactory nerve cell bodies.…”
Section: Symptoms Associated With Increased Icpmentioning
confidence: 63%
“…Patients with IICH often show decreased olfactory bulb volumes91 and impaired olfactory function 9. These findings have also been reported for patients with FM 3. It is most likely that these symptoms are due to increased pressure compromising the blood supply and damaging the olfactory nerve cell bodies.…”
Section: Symptoms Associated With Increased Icpmentioning
confidence: 63%
“…We previously showed that olfactory dysfunction can be seen in a number of autoimmune diseases such as: SLE, multiple sclerosis and myasthenia gravis (MG) [ [43] , [44] , [45] ]. As for the above mention clear association between autoimmunity and the current COVID-19 pandemic, the recent observation of high prevalence of olfactory dysfunction, especially in the early presentation in COVID-19 patients - is not surprising [ 46 ].…”
Section: Loss Of Smell In Sars-cov-2-infected Patients and In Autoimmmentioning
confidence: 99%
“…[2]. The symptoms reported in FM, besides chronic widespread pain and tenderness, include diffuse stiffness, irritable bowel syndrome, fatigue/tiredness, thinking or memory problems, muscle weakness, headache, pain/cramps in the abdomen, numbness/tingling, dizziness, insomnia, depression, pain in the upper abdomen, pelvic pain, vulvodynia, nausea, nervousness, chest pain, blurred vision, fever, dry mouth, itching, wheezing, Raynaud’s phenomenon, hives/welts, ringing in the ears, vomiting, heartburn, oral ulcers, loss of/change in taste, hyposmia, seizures, dry eyes, shortness of breath, loss of appetite, rash, sun sensitivity, hearing difficulties, easy bruising, hair loss, frequent urination, painful urination and bladder spasms, orthostatic intolerance, and temporomandibular joint dysfunction [2,5,6,7]. A modified version of the 2010 criteria has replaced the physician’s estimate of the extent of somatic symptoms with the sum of six self-reported symptoms (fatigue, trouble thinking or remembering, waking up unrefreshed, pain or cramps in the lower abdomen, depression, and headache), making it simpler to use and maintaining sensitivity [8].…”
Section: Introductionmentioning
confidence: 99%